STUDI LITERATUR : PENERAPAN UPAYA PENINGKATAN HARGA DIRI RENDAH DENGAN TERAPI AKTIFITAS KELOMPOK (STIMULASI PRESEPSI) - Widyawati; Bela Purnama Dewi (LPPM STIKes Mitra Adiguna, 2022)
The World Health Organization (WHO), explains that globally an estimated 264 million people are affected by depression. Group Activity Therapy (TAK) perceptual stimulation is one of the modalities of therapy carried out by nurses on a group of patients who have the same nursing problem with the way the patient is trained to prepare the stimulus provided or the stimulus experienced. The purpose of this study was to find out how the implementation of efforts to increase low self-esteem with group activity therapy (stimulation of perception). The design of this study was to use the literature study method. The data source in this study used secondary data obtained by conducting a literature study from journals that were in accordance with the research topic from 2015-2020 as many as 10 journals. Based on the literature review that researchers have done, it can be concluded that: group activity therapy stimulation of perception; Telling about positive experiences you have aims to find out the importance of self-esteem, identify positive things about yourself, train positive things for yourself, the importance of positive things from others, identify the importance of positive things in others and can train positive things in others. As well as changing destructive and maladaptive behaviors. Suggestions are expected that the hospital or health service manager should need to hold training for nursing staff in a planned, and sustainable manner related to the problem of implementing efforts to increase low self-esteem with group activity therapy (stimulation of perception).